Meningkatkan Keterwakilan Perempuan di Ruang Publik dan Politik: Pendidikan Politik Perempuan dalam Program ‘Sekoper Cinta’ di Desa Cimuja, Kecamatan Cimalaka, Kabupaten Sumedang, Provinsi Jawa Barat - Tiara Navy Argawidyanti; Teguh Ilham; Agni Grandita Permata Sari (Lembaga Pengabdian Masyarakat Institut Pemerintahan Dalam Negeri, 2022)
Women's empowerment is needed to eliminate various forms of discrimination in the social, economic and political fields that still occur until today. The empowerment activities which were carried out on March 23 and 24 2022 aim to minimize these problems, namely by educating 100 women in Cimuja Village on the topic of women's representation in public and political sphere. The methods used are lectures, questions and answers, simulations, and group activities. This activity, which is part of the 'Sekoper Cinta' Program in West Java Province, went well, as evidenced by the enthusiasm of the participants. It is hoped that similar programs can be carried out in other regions so that gender equality can be achieved nationally.